Faktor yang Berhubungan dengan Perilaku Pengunjung dalam Membuang Sampah di Pantai Lampu Satu Kabupaten Merauke Papua - Besse Suwito Dwi Asih; Dyah Suryani; Surahma Asti Mulasari (Syntax Literate, 2023)
Traveling means visiting a new place that is different from where you currently live. Clean, beautiful and well-maintained beach conditions will make tourists more comfortable when traveling. However, damage to the coastal environment can occur due to human activities. The aim of this research is to determine the factors related to visitor behavior in throwing away rubbish at Lampu Satu Beach, Merauke Regency, Papua. The research design used is a cross-sectional research design. The sample was visitors to Lampu Satu Beach, Merauke Regency, Papua with a sample size of 321 samples. The statistical test used is the chi square test. Based on univariate analysis, the results showed that 139 (43.3%) respondents had good waste disposal behavior, 129 (40.2%) respondents had high knowledge, 128 (39.9%) respondents had a positive attitude, mature age < 46 as many as 306 (95.3%), respondents with female gender as many as 172 (53.6%), respondents with primary-secondary education 231 people (72.0%), respondents working as many as 171 (53.3%). Bivariate analysis showed that there was a significant relationship between knowledge (p=0.032), attitude (p=0.020), no significant relationship between age (p=1.000), gender p=0.818), education (p= 0.384), and occupation (p=0.210) with trash throwing behavior at Lampu Satu Beach. The approach involves educating beach visitors about awareness and the importance of caring for the surrounding environment. Involve influential community figures in changing the behavior of littering so that visitors are motivated to protect the beach environment.